Antibodies to β2-Glycoprotein I Inhibit Phospholipid Dependent Coagulation Reactions - Brandt, John T (Thrombosis and Haemostasis, 1993)
Lupus anticoagulants are antibodies that inhibit phospholipid dependent coagulation reactions in vitro. These antibodies are of clinical interest because of their association with a variety of clinical manifestations characterized by microvascular thrombosis. Although these antibodies were originally thought to be directed at negatively charged phospholipid, recent studies have suggested that they may be directed at phospholipid-protein complexes. The effect of antibodies directed against β2-glycoprotein I (β2-GP I, apolipoprotein H) on phospholipid-dependent coagulation reactions has been studied. Polyclonal and monoclonal antibodies to β2-GP I were found to inhibit thrombin generation in a dose dependent manner. Inhibition of thrombin formation was due to specific interaction with β2-GP I. There was no evidence that inhibition was due to crossreactivity with other proteins involved in the prothrombinase complex. These findings document that antibodies directed against β2-GP I can have anticoagulant activity analogous to lupus anticoagulant activity and are consistent with the recent observation of such activity in lupus anticoagulant patient samples.